A individualidade nos escritos ontológicos de Lukács - Lucas Souza da Silva (2015)
The Lukacsian writings in the period of maturity, especially the Ontology of social being, aim to characterize, by the not eliminative relationship between man and other natural beings, the determining categories in human self-constitution, which print their specificity. Recognizing sociality as the distinctive feature of man's being, Lukacs intends, by retaking the Marxian work, to follow the historical and ontological path of the potential becoming man of man - the slow, contradictory and unequal human socialization process. From two interdependent poles, social totality and individual, the Lukács’ identification of the social being fulfills a prominent role within our considerations. Indeed, this thesis is especially concerned with the investigation of this mutual determination, by following the way of emergency, consolidation and the process of complexity of individuality. In view of the above object, we pursue, within the Lukacsian ontology, the route by which man changes from a mere natural uniqueness to a socially constituted individuality. We have as the structural axes of this dissertation: the questioning about the way this development is conceived; the identified social mediations; the role assigned to categories such as work, the reproduction and ideology in the social self-constitution of the individual, as well as the impasses recognized as barriers to the effective implementation of the general possibilities of individuals.